The Development of the Framework for Research Ethics in Terrorism Studies (FRETS) - Bont, Eke (Terrorism and political violence, 2021)
This article introduces readers to the Framework for Research Ethics in Terrorism Studies (FRETS). FRETS has been developed to assist IRB/HREC chairs and reviewers in completing reviews of terrorism studies ethics proposals, in as objective a manner as possible. The framework consists of a series of yes/no questions for chairs and reviewers to answer before completing their reviews. These questions are divided into six different sections: participant’s right’s, safety and vulnerability; informed consent; confidentiality and anonymity; researcher’s right’s, safety and vulnerability; data storage and security-sensitive materials; and the ethical review process. This framework was developed as a result of critical analysis of the literature in terrorism research and analogous fields.